ALGORITMA FILTER KALMAN UNTUK MENGHALUSKAN DATA PENGUKURAN - Rudiyanto .; Budi Indra Setiawan; Satyanto Krido Saptomo (Jurnal Keteknikan Pertanian, 2006)
ABSTRACT The objective of this paper is to apply a simple algorithm of Kalman Filter, wich is know as noise data filtering. The computer program was written in Macro Visual Basic in MS Exel. Testings were carried out on available temperature, Water level and force data and then were comared with the mooving average method. The result shows that the algorithm performed better and lesser deviation than the mooving average. Keyword: Kalman Filter, mesurement data, computer program Diterima: 30 Oktober 2006; Disetujui: 14 Nopember 2006